Integrasi Google Maps Dalam PMRI: Analisis Kemampuan Representasi Matematis Pada Materi Matriks - Elvina, Nova; Zulkardi; Susanti, Ely; Meryansumayeka (Lattice Journal : Journal of Mathematics Education and Applied, 2024)
This study aims to analyse students' mathematical representation understanding on matrix material through the integration of real context-based technology. The problem raised in this research is the low ability of students in connecting matrix concepts with real-life situations. To answer these problems, this research used a descriptive qualitative approach with a case study design. The research subjects involved 29 grade XI students at SMK Negeri 1 Sekayu, who were grouped into seven groups. The sampling technique was purposive, while data were collected through tests and questionnaires. The data were analysed descriptively to identify students' mathematical representation patterns, including pictorial, symbolic and verbal representations. The results showed that the integration of Google Maps in matrix learning strengthened students' conceptual understanding through real spatial visualisation. This approach significantly improves students' ability to represent mathematical concepts, as well as encourages motivation, engagement and collaboration during the learning process. In addition, the findings underline the relevance of the real context-based approach in Indonesian Realistic Mathematics Education (PMRI), which makes learning more applicable and meaningful. The conclusion of this study is that the integration of Google Maps has a positive influence on students' mathematical representation skills, especially on matrix material. For future research, it is recommended to explore the application of similar technology in other mathematics materials and analyse its effect on students' problem solving.   Translated with DeepL.com (free version) Penelitian ini bertujuan untuk menganalisis pemahaman representasi matematis siswa pada materi matriks melalui integrasi teknologi berbasis konteks nyata. Permasalahan yang diangkat dalam penelitian ini adalah rendahnya kemampuan siswa dalam menghubungkan konsep matriks dengan situasi kehidupan sehari-hari. Untuk menjawab permasalahan tersebut, penelitian ini menggunakan pendekatan deskriptif kualitatif dengan desain studi kasus. Subjek penelitian melibatkan 29 siswa kelas XI di SMK Negeri 1 Sekayu, yang dikelompokkan ke dalam tujuh kelompok. Teknik sampling dilakukan secara purposif, sementara data dikumpulkan melalui tes dan angket. Data dianalisis secara deskriptif untuk mengidentifikasi pola representasi matematis siswa, meliputi representasi gambar, simbolik, dan verbal. Hasil penelitian menunjukkan integrasi Google Maps dalam pembelajaran matriks memperkuat pemahaman konseptual siswa melalui visualisasi spasial yang nyata. Pendekatan ini secara signifikan meningkatkan kemampuan siswa dalam merepresentasikan konsep matematis, serta mendorong motivasi, keterlibatan, dan kolaborasi selama proses pembelajaran. Selain itu, temuan ini menggarisbawahi relevansi pendekatan berbasis konteks nyata dalam Pendidikan Matematika Realistik Indonesia (PMRI), yang menjadikan pembelajaran lebih aplikatif dan bermakna. Kesimpulan dari penelitian ini adalah bahwa integrasi Google Maps memberikan pengaruh positif terhadap kemampuan representasi matematis siswa, terutama pada materi matriks. Untuk penelitian selanjutnya, disarankan untuk mengeksplorasi penerapan teknologi serupa pada materi matematika lainnya dan menganalisis pengaruhnya terhadap pemecahan masalah siswa